(untitled) (Fiep Bulletin - online, 2017)
The article seeks to present a public policy model for healthy and active aging, sponsored by the City of Rio de Janeiro,through SEMEARC - Municipal Aging and Care Resilience. Population aging in Brazil has been growing for decades and everydecade the population growth projection over 60 years Veras (2001) confirms this fact by suggesting that the longevity of thepopulation is a world phenomenon, and that Brazil is a clear example of this process is characterized by absolute and relativeincrease. The decrease in fertility and mortality rates has been altering the age structure of the population, leading to a markeddecrease in mortality rates, particularly in the first years of life (ASSIS, 2005). Thus the application of a policy geared to the care ofthe elderly would be the guarantee of productive people and less spending on Sude system, and provide continuity in the positiveand beneficial actions of the population.